The client’s value model proposal from the marketing-rentability perspective to apply into touristic companies: Propuesta de un modelo de valoración del cliente desde la perspectiva marketing-rentabilidad para aplicar en empresas turísticas - Guadarrama Tavira, Enrique (2015)
The quality of touristic services’ demand will be increased in the next decades. So, the tourist organizations should put into practice actions aim to recognize the value that their clients provide and draw the commercial strategies lead to change from a massive marketing to a personalized attention which leads to the satisfaction and fidelity to clients who provide the most. In order to obtain it, in this current article it is adopted as an objective to propose an evaluation model which gathers variables that influence in the client ́s value from the rational marketing perspective, based on the reflexion of investigation done with clients regarding to their values. As conclusion it is said that the linking marketing is considered as a key business strategy to adapt to the current times. In the tourist sector it acquires relevance and priority due to its direct contribution to increase the operations and sales volumes of companies against the vulnerable activity to the clients’ negative perceptions and to the influence of their recommendations in the end results of these organizations. The quality and the satisfaction are considered as the main variable which will permit to distinguish the fidelity of the client